Classroom Techniques Used In Speaking Activities InEnglish Classroom: A Naturalistic Study At SMPMuhammadiyah 1 Kartasura In 2015/2016 Academic Year - Puspitaningrum, Diyah; , Prof. Dr. Endang Fauziati, M. Hum; , Siti Fatimah S. Pd., M. Hum (2016)
This study is carried out to describe classroom techniques used in speaking activities in English classroom at SMP Muhammadiyah 1 Kartasura. The aims of this research are: (1) to describe the kinds of classroom techniques used in speaking activities, (2) the purpose of using each classroom techniques, (3) the teacher's roles, (4) the student's roles, (5) instructional materials used by the English teachers at SMP Muhammadiyah 1 Kartasura. The kind of this research is descriptive qualitative research especially naturalistic study in analyzing the data. The methods of collecting data in this research are observation, interview and document. The finding of the study shows that there are some classroom techniques used by English teachers at SMP Muhammadiyah 1 Kartasura such as: role playing, discussion and problem solving. Teacher has role as model, instructor, teaching knowledge and facilitator, controller, evaluator and manager. The student has role as participant, demonstrate their knowledge and understanding, student's dialog and interaction with teacher, as learner member group and learn by Interact with other, as tutor the learners. And the instructional material is text book such as handbook and LKS. The conclusion of this research is that English teacher at SMP Muhammadiyah 1 Kartasura used various classroom techniques which can improve the students' ability. Various techniques can make the student interested in English teachinglearning process. It does not make the class monotonous. The students become more active and creative. Based on the result, apparently, classroom techniques used by the teacher have important role in the teaching-learning process.